Pangs of love & other writings - Louie, David Wong, 1954-2018 (Classics of Asian American literature., 2019)
"Pangs of Love, originally published in 1991, was the debut work of David Wong Louie, one of the most influential voices in contemporary Asian American literature. This collection of short stories centers around characters who are in conflict with their place in the world, often feeling disconnected from both American society and their own families. Yet the stories transcend the simplistic narrative of Asian American struggles with alienation in a foreign land, and the depth of the characters highlights how their experiences of love and envy and loneliness and loss and duty are universal, informed by their heritage but not confined by it. This expanded edition includes an additional short story, a haunting autobiographical essay, an afterword by King-Kok Cheung, and a foreword by Pulitzer Prize winner Viet Thanh Nguyen"--